Networks of denunciation and propaganda between Spain and Argentina: culture in the "external front" of the dictatorship (1976-1983) (Quinto Sol, 2024)
In the context of the Spanish transition to democracy, Argentine exiles who sought refuge in Spain after the last civil-military dictatorship (1976-1983) suffered surveillance, infiltration and control by representatives of the political regime and agents of its intelligence services. This article examines this double presence of Argentine citizens in Spanish territory and its local articulations, focusing on the study of two experiences that allow us to appreciate the military regime's concern to spread a positive image outside its borders. Both the invitation by the dictatorship to the Spanish writer and journalist Fernando Vizcaíno Casas to visit Argentina, and the official participation in the First Congress of Spanish-Speaking Writers, both in 1979, reveal themselves to be strategies to counteract the international denunciations of which the Military Junta was the target. Based on the crossing of certain available documentary and testimonial sources, the historical reconstruction of the aforementioned events helps to reflect on the modes of operation of these opposing networks of denunciation and propaganda, their points of contact and interaction. The hypothesis proposed is that the local and national inscription of the Argentine political struggle was linked to the Spanish political agenda, in a territory with great symbolic weight for the history of the South American country.
Keywords: dictatorship; propaganda; intellectuals; foreign relations